SEJARAH PUSAT DOKUMENTASI DAN INFORMASI KEBUDAYAAN MINANGKABAU (PDIKM) KOTA PADANG PANJANG (1988-2022) - Gustina Rahma; Suriani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The main thing that forms the basis of the background for this writing is to inform the wider public that west Sumatra has established a Minangkabau culture, especially ror researchers and students who want to get sources without having togoto the NI museum in Jakarta or the Leiden museum in the Netherlands, which are very far away. Now PDIKM has provided various kinds of collections related to Minangkabau cultural information. The author’s type of data collection is qualitative, descriptive- analytic in nature. This research method is a historical research method using heuristic stages, source criticism, interpretation and historiography. The results of this research show that the groundbreaking of the PDIKM Museum was established on January 8 1988 and was inaugurated two years later on December 19 1990. The collections at PDIKM have increased over time due to various efforts made by the Foundation. The condition of the collected collections is very well cared for by the Foundation. However, to ensure better management, the Foundation granted its management to the Padang Panjang Regional Government from 1007-2015 but the assets are still in the name of the Foundation. Then, from 2015 until now the assets have been handed over to the Padang Panjang Disporapor, since then the management and condition of the collection has been much better.